2017
DOI: 10.1007/s13346-017-0371-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and evaluation of a peptide-based siRNA delivery system in vitro

Abstract: Since its inception more than a decade ago, gene silencing mediated by double-stranded small interfering RNA (siRNA) has been widely investigated as a potential therapeutic approach for a variety of diseases. However, the use of siRNA is hampered by its rapid degradation and poor cellular uptake in vitro and in vivo. Recently, peptide-based carriers have been applied to siRNA delivery, as an alternative to the traditional delivery systems. Here, a histidine-containing amphipathic amino acid pairing peptide, C6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
0
11
1
Order By: Relevance
“…However, obvious hemolysis was detected when the pH of the culture media was 5.7, and the lytic activity showed concentration dependence. Previous work demonstrated that the EC 50 (the concentration of free peptide for 50% hemolysis) value of C6M3 was ∼16 μg mL −1 , 52 which was much lower than those in our work (29.7, 27.0 and 33.8 μg mL −1 for PDMAEMA-C6M3, PEI-C6M3 and PLL-C6M3, respectively). This may be attributed to the fact that the conjugation of C6M3 to polycations compromises the lytic activity.…”
Section: Hemolysis Testing Of the Polycationscontrasting
confidence: 88%
See 1 more Smart Citation
“…However, obvious hemolysis was detected when the pH of the culture media was 5.7, and the lytic activity showed concentration dependence. Previous work demonstrated that the EC 50 (the concentration of free peptide for 50% hemolysis) value of C6M3 was ∼16 μg mL −1 , 52 which was much lower than those in our work (29.7, 27.0 and 33.8 μg mL −1 for PDMAEMA-C6M3, PEI-C6M3 and PLL-C6M3, respectively). This may be attributed to the fact that the conjugation of C6M3 to polycations compromises the lytic activity.…”
Section: Hemolysis Testing Of the Polycationscontrasting
confidence: 88%
“…51 Previous studies showed that the C6M3 peptide (a peptide derived from C6) features pH-triggered lytic activity, and promising membrane lysis was observed under endo/lysosomal acidic conditions rather than at a normal pH value. 51,52 We hypothesize that the incorporation of polycations with C6M3 could not only enhance the gene delivery efficiency through the promotion of endo/lysosomal escape but also avoid off-site toxicity. As shown in Scheme 1, the C6M3 modified polycations condense DNA into nanoparticles, which can be endocytosed by cells through the endosome pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the therapeutic application of miRNA mimics is limited due to their low capacity to penetrate cell membranes due to their negative charge. 70 To date, many substances have been assessed for the delivery of nucleic acids, including CPPs, but there is still a lack of efficient, safe, and specific methods for the in vivo delivery of potentially therapeutic nucleic acids, including miRNA mimics. 71,72 We previously demonstrated the capacity of CPP-miR-146a noncovalent nanocomplexes to suppress inflammatory responses in cell cultures and a mouse model of irritant contact dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of new drugs able to bind doublestranded DNA, as well as to interfere with double-stranded RNA-driven biological processes [39][40][41] or act as stabilizers and carriers of double-stranded RNA drugs, [42][43][44][45][46] prompted us to study the interaction of oligoDapT with dA 12 /dT 12 and poly(rA)/poly(rU), chosen as double-stranded DNA and RNA model systems, respectively. First, the target complexes were prepared by mixing equimolar amounts of DNA and RNA single strands, heating the resulting solutions at 90°C for 10 minutes and then slowly cooling overnight.…”
mentioning
confidence: 99%